Multi-level Governance of Integration Policy. Role of the Cities. Comparison of Warsaw and Prague - Matusz, Patrycja; Pawlak, Mikołaj (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2020)
This paper analyses the role of the cities in the multi-level governance of integration policy. The goal was to analyse the relations of diverse actors in a multi-level governance context and the direct impact of the transnational EU policy to local level actors (that also bypassed the national level). We show how the interconnection of policy levels and the presence of actors in many roles in the process of developing immigrant integration policies resulted in the top-down transfer of policy goals. We also highlight the converse perspective and demonstrate how bottom-up policy initiatives strengthen the position of cities as important players in the multilevel governance, both individually and collectively.

Artykuł dotyczy wielopoziomowego zarządzania polityką integracji migrantów w miastach. Celem artykułu jest analiza relacji różnych aktorów w kontekście wielopoziomowego zarządzania polityką integracyjną, w szczególności oddziaływania transnarodowej polityki UE na aktorów szczebla lokalnego (proces by-passing national level). Tekst zwraca uwagę na wzajemne powiązanie poziomów polityki i obecność aktorów w wielu rolach w procesie tworzenia polityk integracji imigrantów. Procesy te skutkowały odgórnym transferem celów polityki. Artykuł zwraca również uwagę perspektywę odwrotną i pokazuje, jak oddolne inicjatywy polityczne wzmacniają pozycję miast jako ważnych graczy w wielopoziomowym zarządzaniu, zarówno indywidualnie, jak i zbiorowo.
Wielopoziomowe zarządzanie polityką integracji. Rola miast. Porównanie Pragi i Warszawy
Keywords: multi-level governance; integration policy; migration; cities; migrants; local level; wielopoziomowe zarządzanie; polityka integracyjna; migracja; miasta; migranci; poziomo lokalny